The Buzz Group Method Influences Students' Knowledge in Learning Cardiac Resuscitation Skills in Infants - Padila, Padila; Andri, Juli; Andrianto, Muhammad Bagus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine whether the Buzz Group Method affects students' knowledge in learning Cardiopulmonary Resuscitation Skills in Infants. This type of research is pre-experimental with a one-group pretest-posttest design. The research results obtained a p-value of 0.000 < 0.05, and the results of the correlation test obtained r = 0.524 with a p-value of 0.003 < alpha (0.05) and had a positive pattern. In conclusion, the Buzz Group method influences the level of cardiopulmonary resuscitation knowledge of nursing students at Muhammadiyah University of Bengkulu, and there is a relationship between the level of expertise and students' cardiopulmonary resuscitation skills. Keywords: Buzz Method, Knowledge, Cardiopulmonary Resuscitation